Efficacy of Physiotherapy in Improving the Range of Motion of Elbow after the Treatment of Pediatric Supracondylar Humeral Fracture - Jha, Subash Chandra; Shakya, Prakash; Baral, Pramod (Birat Journal of Health Sciences, 2018)
Introduction: Temporary stiffness of elbow range of motion (ROM) after treatment of supracondylar humeral fracture in children is often a parental concern. Objectives: We examined the role of physiotherapy in improving the elbow ROM in management of supracondylar humeral fracture in children. Methodology: Sixty-four patients were randomly divided into intervention and control groups. Then intervention group patients received regular physiotherapy sessions while control group patients were not sent for physiotherapy. We assessed the outcome according to Flynn criteria during their follow-ups at two, six and 12 weeks, after removal of cast/k-wires. Results: In intervention group, 77.4% children had excellent outcome, and in control group, 80.6% children had excellent outcome. However, we did not find any statistically significant association between physiotherapy and outcome at 12 weeks, after controlling for baseline characteristics in multivariable regression model. Conclusion: Children managed by close reduction for uncomplicated supracondylar humeral fracture with immobilization for three weeks regain their functional ROM within 12 weeks of mobilization by themselves, with no added benefit from physiotherapy. BJHS 2018;3(2)6: 432-436.